2021
DOI: 10.1002/ange.202103222
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Wacker‐type Oxidation of Olefins at Room Temperature with 1,3‐Diketones or Neocuproine as Ligands**

Abstract: Herein, we describe a convenient and general method for the oxidation of olefins to ketones using either tris(dibenzoylmethanato)iron(III) [Fe(dbm)3] or a combination of iron(II) chloride and neocuproine (2,9‐dimethyl‐1,10‐phenanthroline) as catalysts and phenylsilane (PhSiH3) as additive. All reactions proceed efficiently at room temperature using air as sole oxidant. This transformation has been applied to a variety of substrates, is operationally simple, proceeds under mild reaction conditions, and shows a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…We have an ongoing project directed towards the application of iron compounds as catalysts for convenient oxidative transformations, since iron compounds represent environmentally benign catalysts [30,31] . In this context, we found that the hexadecafluorophthalocyanine–iron(II) complex FePcF 16 , [32,33] which under air is immediately oxidized to μ‐oxo‐bis[(hexadecafluorophthalocyanine)iron(III)] (O[FePcF 16 ] 2 ) (Figure 2), [33f] shows exceptional reactivity as catalyst for the oxidative C−C homocoupling reaction of diarylamines 3 to 2,2′‐bis(arylamino)‐1,1′‐biaryl compounds 4 [34a,b] .…”
Section: Resultsmentioning
confidence: 99%
“…We have an ongoing project directed towards the application of iron compounds as catalysts for convenient oxidative transformations, since iron compounds represent environmentally benign catalysts [30,31] . In this context, we found that the hexadecafluorophthalocyanine–iron(II) complex FePcF 16 , [32,33] which under air is immediately oxidized to μ‐oxo‐bis[(hexadecafluorophthalocyanine)iron(III)] (O[FePcF 16 ] 2 ) (Figure 2), [33f] shows exceptional reactivity as catalyst for the oxidative C−C homocoupling reaction of diarylamines 3 to 2,2′‐bis(arylamino)‐1,1′‐biaryl compounds 4 [34a,b] .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the same group developed more effective iron catalytic systems based on a hexacoordinated iron III complex comprising three O , O -chelating dibenzoylmethanato(dbm) [Fe(dbm) 3 ] ligands or an in situ combination of FeCl 2 and the N , N -chelating neocuproine ligand, thereby pushing the boundaries of the sustainable Wacker-type oxidation (Scheme 6 ). 25 In the presence of PhSiH 3 , these iron catalytic systems did not work for aromatic olefins and aliphatic olefins, even internal examples.…”
Section: Reductive Activation Strategies For Oxygenationmentioning
confidence: 99%
“…Pushing the boundaries of sustainable Wacker‐type oxidations, the Knölker group reported in 2021 the first examples of iron catalysts operating in an air atmosphere and at room temperature with Markovnikov selectivity [29] . The precatalysts are based on a hexacoordinated iron(III) complex comprising three O , O ‐chelating dibenzoylmethanato (dbm) ligands or an in situ combination of FeCl 2 and the N , N ‐chelating neocuproine ligand (Scheme 11).…”
Section: Iron‐based Catalysts For Wacker‐type Reactionsmentioning
confidence: 99%